Cause-specific mortality among HIV-infected people in Ontario, 1995–2014: a population-based retrospective cohort study - Burchell, Ann N. (CMAJ Open, 2019)
BACKGROUND: Risk factors for cause-specific mortality have not been widely studied among people with HIV infection. Our objectives were to estimate rates of and risk factors for all-cause and cause-specific mortality from 1995 to 2014 among HIV-infected people in Ontario. METHODS: We conducted a population-based retrospective cohort study using provincial health databases of people with HIV infection who were aged 16 years or more, were residents of Ontario between 1995 and 2014, and had HIV infection according to a previously validated algorithm. We used International Classification of Diseases codes to classify the underlying cause of death and estimated age-adjusted mortality rates per 100 person-years for 1995 to 2014. We used descriptive statistics to characterize the cohort at baseline and calculated adjusted mortality rate ratios (RRs) using generalized estimating equations. RESULTS: Among 23 043 people, the all-cause mortality rate declined from 6.69 to 1.53 per 100 person-years over the study period, and the rate of death from HIV/AIDS declined from 4.75 to 0.46 per 100 person-years. Concomitantly, the proportions of deaths due to cancer, cardiovascular disease and other noncommunicable diseases rose; however, rates remained constant or declined. Compared to males, females had higher mortality due to cardiovascular disease (adjusted RR 1.36, 95% confidence interval [CI] 1.04–1.77), noncommunicable causes (adjusted RR 1.75, 95% CI 1.39–2.20) and, by 2010–2014, any cause (adjusted RR 1.19, 95% CI 1.02–1.38). Residing in a low-income neighbourhood was associated with increased risk for most causes, including HIV/AIDS (adjusted RR in 2010–2014 1.86, 95% CI 1.49–2.31). Rural residence was associated with increased mortality due to malignant disease (adjusted RR 1.60, 95% CI 1.10–2.34) and noncommunicable disease (adjusted RR 1.86, 95% CI 1.25–2.77). Being an immigrant was associated with lower risk of death from all causes. INTERPRETATION: Over the study period, death was increasingly due to common chronic conditions rather than to HIV infection itself. Care should incorporate the prevention and management of these conditions, especially among females and those residing in rural and low-income areas.